PENGUKURAN TINGKAT KONDISI FISIK MENGGUNAKAN BATTERY TEST PADA PEMAIN FUTSAL UNGGUL FC MALANG - Imanto, Yuniar; Himawan, Agus; Widodo, Haryo Mukti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the Level of Physical Condition Using Battery Test on Unggul FC Malang Futsal Players. This study is included in the type of descriptive research with a quantitative approach. The sample in this study were KU athletes trained by Unggul FC Malang, The research variable is the physical condition of KU Unggul FC Malang futsal players, with the instrument used in the form of a series of physical condition tests through Battery Test which includes strength, flexibility, speed, and agility. The results of the battery test for flexibility obtained an average of 18.11 ± 7.97, an average speed of 3.31 ± 0.16, an average agility of 16.52 ± 0.74, and an average strength of 41.83 ± 0.74. The conclusion of this study is that the physical condition of Unggul FC Malang futsal players is in a fairly good category, although there is still room for improvement, especially in terms of flexibility which has large variations among players. A more specific and targeted training program is needed to improve each component of physical condition so that team performance can be more optimal.